1996
DOI: 10.1172/jci118523
|View full text |Cite
|
Sign up to set email alerts
|

A novel heparin-dependent processing pathway for human tryptase. Autocatalysis followed by activation with dipeptidyl peptidase I.

Abstract: Tryptase is the major protein constituent of human mast cells, where it is stored within the secretory granules as a fully active tetramer. Two tryptase genes ( ␣ and ␤ ) are expressed by human mast cells at the level of mRNA and protein, each with a 30 amino acid leader sequence. Recombinant precursor forms of human ␣ -and ␤ -tryptase were produced in a baculovirus system, purified, and used to study their processing. Monomeric ␤ -protryptase first is shown to be intermolecularly autoprocessed to monomeric ␤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 37 publications
2
97
0
Order By: Relevance
“…Although Mirza et al (31) were able to obtain enzymatically active tryptase ␣ in transiently transfected COS cells, Sakai et al (32) concluded that this human MC protease probably is not on recombinant mouse tryptases have revealed that this family of serine proteases must spontaneously form a tetramer to become enzymatically active. It is therefore assumed that the percentage of pseudozymogen in each preparation which is converted by EK into active enzyme is the same.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Mirza et al (31) were able to obtain enzymatically active tryptase ␣ in transiently transfected COS cells, Sakai et al (32) concluded that this human MC protease probably is not on recombinant mouse tryptases have revealed that this family of serine proteases must spontaneously form a tetramer to become enzymatically active. It is therefore assumed that the percentage of pseudozymogen in each preparation which is converted by EK into active enzyme is the same.…”
Section: Discussionmentioning
confidence: 99%
“…The latter investigators noted that the propeptide of tryptase ␣ differs from that of mouse, rat, and other human tryptase zymogens at residue Ϫ3. Based on their inability to obtain active enzyme in an insect cell expression system, Sakai et al (32) concluded that all tryptases probably undergo an unusual multistep activation process in MCs that is exquisitely heparin-dependent. To explain their in vitro findings, these investigators proposed that a conformation-dependent change occurs when a tryptase zymogen initially binds to heparin, which in turn causes a partial autocatalytic event resulting in the removal of the first 8 residues of the propeptide.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant human ␤-protryptase can be activated in vitro by two sequential steps of propeptide processing (7). First, ␤-protryptase is autoprocessed to the inactive intermediate proЈ-tryptase, which has a residual pro-dipeptide.…”
Section: Table I Protease Activity In Bmmc Lysatesmentioning
confidence: 99%
“…Available evidence suggests that activation of tryptases is more complicated than that of chymases and other granule-associated serine proteases. In vitro studies indicate that, after removal of a signal peptide by signal peptidase, human ␤-tryptase requires two additional, sequential cleavages of its propeptide for activation (7). The first such cleavage is thought to be by tryptase itself, which leaves a two-amino acid activation dipeptide to be removed by DPPI.…”
mentioning
confidence: 99%